2011
DOI: 10.1111/j.1600-0528.2011.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral status, oral hygiene habits and caries risk factors in home‐dwelling elderly dependent on moderate or substantial supportive care for daily living

Abstract: Good oral hygiene habits were associated with less prevalence of plaque and oral disease in the elderly irrespective of extent of needs of home nursing. However, the elderly with moderate needs more often performed good self-care, indicating that the possibilities of strengthening self-care and learning new routines are better when functions are less affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 24 publications
(30 reference statements)
5
77
1
5
Order By: Relevance
“…The same holds true for the participants; there is no placebo treatment available and therefore, participants in the control group receive ´care as usual´. This ´care as usual´ for dependent elderly could, and one might even argue, should, include oral health care, but it has been shown that this is often unfortunately not the case (e.g., [26,28,57-60]). In contrast to the nursing staff and the participants, the trained examiners are blinded for the participants’ allocation in either the intervention or control group.…”
Section: Discussionmentioning
confidence: 99%
“…The same holds true for the participants; there is no placebo treatment available and therefore, participants in the control group receive ´care as usual´. This ´care as usual´ for dependent elderly could, and one might even argue, should, include oral health care, but it has been shown that this is often unfortunately not the case (e.g., [26,28,57-60]). In contrast to the nursing staff and the participants, the trained examiners are blinded for the participants’ allocation in either the intervention or control group.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy allowed us to identify common patterns in responses across people with maximum variation in variables that are known to influence the oral health behavior of the target group: age [22,26-28], gender [26,27], dental status [15,22,28,29], institutionalization [13,14] and type and intensity of care they receive as a measure for frailty [15,16,20,21,30,31]. …”
Section: Methodsmentioning
confidence: 99%
“…However, despite extensive research on barriers to dental service-use [7,12-17] and oral hygiene-related behavior [18-21] in which barriers have been associated with impaired mobility, impaired activities of daily living, low energy, depression, and lack of social support, it remains unclear how frailty in its many forms influences the oral care of older people. For example, it is not clear whether service-use and toothbrushing are disturbed more by impaired mobility, dexterity, or low morale, or, as some [22,23] suggest, by a lack of time and energy caused by more pressing general health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Kwetsbaarheid heeft een negatieve invloed op zowel tandartsbezoek als op mondverzorgingsgedrag (MacEntee, 2011). Onderzoek heeft aangetoond dat verminderde mobiliteit, verminderde fysieke functies, weinig energie, depressie en gebrek aan sociale steun hiermee zijn geassocieerd (Dolan et al, 1998; Kiyak en Reichmuth, 2005;Borreani et al, 2008;Stromberg et al, 2012). Niet bekend is op welke manier kwetsbaarheid en verschillende kwetsbaarheidsfactoren van invloed zijn op de mondverzorging en tandartsbezoek van ouderen.…”
unclassified